Structure-based rational design of covalent probes - Matthew Holcomb; Manuel Llanos; Althea Hansel-Harris; Stefano Forli (Communications Chemistry)
Abstract Covalent probes are becoming increasingly important to both fundamental biology and drug design, as what was once an idiosyncrasy at best and a source of toxicity at worst has transitioned to a paradigm for drug discovery. However, these covalent probes offer different challenges for the incorporation of structural data into the design process than do non-covalent probes, whose activity may be captured by very few bound states. In this review, we discuss the role of structure-based design in the discovery and optimization of covalent probes, with a special emphasis on computational methods to leverage structural data.